The Cooperative Taxation Controversy : a Conceptual and an Econometric Model - Khadija Rhaddioui; Said Ahrouch (PT. EQUATOR SINAR AKADEMIA, 2022)
Cooperatives are an integral and an essential part of the social and solidarity economy, as it has a dual role by contributing greatly to the local socio-economic development. Thereby, these social entities are considered as tools to satisfy the economic and the social Society’s needs. Thus, the cooperatives are subject to several legal restrictions and constraints in relation to the nature of the activity exercised, compared to the counterpart entities. Moreover, to overcome these compulsions, most of government grants these social entities a set of taxes grace. Nevertheless, the activity expansion of certain cooperatives has aroused the demonstration of its competitors arguing that these tax exemptions leads to unfair competition, in return the cooperatives subject to this claim, defend their position by affirming that their activity generate certainly profits, but it contribute greatly to the social aspect. Therefore, the present research consisted in the study of the taxation’s effect on dairy processing cooperatives in Morocco at the commercial, financial and social level in order to resolve this taxation controversy. Thereby, this study was carried out according to a quantitative study on the leading cooperatives of the dairy sector in Morocco, by using the econometric software STATA on the basis of the conceptual and the econometric model appropriate to the research theme.